Mesenchymal Hamartoma With Elevated Alpha-Fetoprotein: A Diagnostic Pitfall - Amine Naggar MD; Hajar Andour MD; Hamza Bensaghir MD; Badr Kabila MD; Chaimae Ben Driss MD; Soukaina El Aouni MD; Monim Ochan PhD; Mounir Kisra PhD; Najat Lamalmi PhD; Siham El Haddad PhD; Nazik Allali PhD; Latifa Chat PhD (SAGE Publishing, 2023)
Mesenchymal hamartoma (MH) is a benign liver tumor accounting for 3% to 8% of all liver tumors in children, commonly manifesting before 3 years of life. Distinguishing MH from hepatoblastoma and other liver tumors relies on imaging and alpha-fetoprotein (which is usually within normal range in MH), before histologic examination. We report a case of a hepatic MH associated with elevated alpha-fetoprotein, leading to a misdiagnosis of hepatoblastoma and the administration of chemotherapy. We draw the attention to the diagnostic difficulty and pitfalls related to alpha-fetoprotein elevation in the setting of a liver tumor, and we highlight the importance of imaging and histology in establishing the diagnosis.